ASSESSMENT OF USERS' SATISFACTION WITH IRRIGATION SERVICE PROVIDED IN HARE IRRIGATION SCHEME, ARBA MINCH, ETHIOPIA - Mamuye Tebebal; Genet Mathewos Messene (International Journal of Innovations in Engineering Research and Technology, 2021)
Farmer’s perspectives and assessments of irrigation scheme performance are critically inherent for irrigation system management. Hare irrigation scheme is indeed expected to play a vital role to realize food security and enhance farm incomes in the rural households. Yet, insufficient farm returns and social factors corresponding to water distribution problems are transpired. The objective of this study was to assess the level of user's satisfaction with irrigation services provided by the scheme in terms of adequacy of water supply, dependability, equity of water distribution, timelines of water delivery, user’s contribution in operation and maintenance activities; operation and maintenance requirements of the system. It was analyzed using Binary Logit model. The study was conducted in the irrigation season from September to December, 2014.